Periodicals Received (Review of Economic Studies, 1936)
Journal Article Periodicals Received Get access The Review of Economic Studies, Volume 3, Issue 3, June 1936, Page 235, https://doi.org/10.1093/restud/3.3.235-a Published: 01 June 1936